Cost-Effectiveness of a Small Intrapericardial Centrifugal Left Ventricular Assist Device. Issue 8 (August 2020) - Silvestry, Scott C.; Mahr, Claudius; Slaughter, Mark S.; Levy, Wayne C.; Cheng, Richard K.; May, Damian M.; Ismyrloglou, Eleni; Tsintzos, Stelios I.; Tuttle, Edward; Cook, Keziah; Birk, Erica; Gomes, Aparna; et al.
Abstract : There is limited data on the cost-effectiveness of continuous-flow left ventricular assist devices (LVAD) in the United States particularly for the bridge-to-transplant indication. Our objective is to study the cost-effectiveness of a small intrapericardial centrifugal LVAD compared with medical management (MM) and subsequent heart transplantation using the respective clinical trial data. We developed a Markov economic framework. Clinical inputs for the LVAD arm were based on prospective trials employing the HeartWare centrifugal-flow ventricular assist device system. To better assess survival in the MM arm, and in the absence of contemporary trials randomizing patients to LVAD and MM, estimates from the Seattle Heart Failure Model were used. Costs inputs were calculated based on Medicare claim analyses and when appropriate prior published literature. Time horizon was lifetime. Costs and benefits were appropriately discounted at 3% per year. The deterministic cost-effectiveness analyses resulted in $69, 768 per Quality Adjusted Life Year and $56, 538 per Life Year for the bridge-to-transplant indication and $102, 587 per Quality Adjusted Life Year and $87, 327 per Life Year for destination therapy. These outcomes signify a substantial improvement compared with prior studies and re-open the discussion around the cost-effectiveness of LVADs. Abstract : Supplemental Digital Content is available in the text.